Peningkatan Hasil Belajar Passing Kaki Bagian Dalam dengan Menggunakan Modifikasi Permainan Sepak Bola pada Siswa SD Negeri 375 Lalong Selatan - Rety, Alghazali; Ahmad, Ahmad; Riswanto, A. Heri; Hidayat, Rachmat; Nur, Suaib (Universitas Hamzanwadi, 2025)
This study aims to improve the learning outcomes of passing using the inner foot with modified soccer games. This research uses the PTK method. The population of this study were all IVa students of SDN 375 Lalong Selatan totaling 25 students divided into two classes. The sample used was all fourth grade students of SDN 375 South Lalong. Data collection techniques carried out tests of inner leg passing ability. The results of this study indicate that in cycle I there were 5 students who were complete, meaning that the classical completeness reached (20%) in the knowledge aspect, there were 9 students who were complete, meaning that the classical completeness reached (36%) in the attitude aspect and there were 10 students who were complete, meaning that the classical completeness reached (40%) in the skill aspect. while in the results of cycle II there were 25 students who were complete, while in the results of cycle II there were 25 students who were complete, meaning that the classical completeness reached (100%) in the knowledge aspect, there were 23 students who were complete, meaning that the classical completeness reached (92%) in the attitude aspect, there were 24 students who were complete, meaning that the classical completeness reached (96%) in the skill aspect. This shows that there is a significant increase between cycle I and cycle II. Thus the modification of soccer games can improve the learning outcomes of inner leg passing.